Correlation of CD4:CD8 ratio and tumour necrosis factor (TNF)α levels in induced sputum with bronchoalveolar lavage fluid in pulmonary sarcoidosis. Issue 8 (1st August 2000) - Moodley, Yuben P; Dorasamy, Trevor; Venketasamy, Salosh; Naicker, Vincent; Lalloo, Umesh G
Abstract : BACKGROUND: An increased CD4:CD8 lymphocyte ratio and raised cytokine levels in bronchoalveolar lavage (BAL) fluid are characteristic of pulmonary sarcoidosis. Sputum induction has been used as a non-invasive tool for investigating the airways and may be useful in investigating inflammation in patients with sarcoidosis in whom endobronchial, peribronchial, and parenchymal inflammation is present. This study aimed to correlate the total and differential cell counts, CD4:CD8 ratio, and tumour necrosis factor (TNF)α levels between induced sputum and BAL fluid in patients with pulmonary sarcoidosis. METHODS: Fourteen patients with newly diagnosed biopsy proven sarcoidosis and six healthy controls were investigated. Sputum induction and BAL was carried out at the initial visit and repeated following six months of treatment with oral prednisone. RESULTS: There was no correlation of differential cell counts between induced sputum and BAL fluid. The CD4:CD8 ratio in induced sputum correlated strongly with that in BAL fluid (5.5 (0.4:1) versus 4.4 (0.2:1); r = 0.8, p<0.001) and the fall in the ratio following six months of treatment in sputum paralleled that in BAL fluid (3.4 (0.2:1) versus 2.4 (0.2:1)). The TNFα levels in sputum also correlated with levels in the BAL fluid (11.9 (1.5) pg/ml versus 17.6 (2.7) pg/ml; r = 0.8, p<0.001). The fall in sputum TNFα levels following six months of treatment paralleled the fall in BAL fluid levels (6.7 (0.9) pg/ml versus 11.6 (1.3) pg/ml). CONCLUSIONS: The CD4:CD8 ratio and TNFα levels in induced sputum correlated with those in BAL fluid and paralleled changes with treatment. Induced sputum may therefore be a non-invasive surrogate for certain parameters in BAL fluid in patients with sarcoidosis.